PENGARUH TERAPI AKUPRESURE TERHADAP PENURUNAN TINGKAT NYERI HAID (DISMENORE) PADA REMAJA - Dewi, Ratna; Juwita, Lisavina; Lazdia, Weny; Wati, Rahmi; Bunga, Weni; Syukri, Rahmat (Universitas Fort De Kock, 2024)
ABSTRACTMenstrual pain, also known as dysmenorrhea, is caused by an imbalance of progesterone hormones in the blood, resulting in recurring pain that disrupts daily activities. Acupressure, a therapy involving finger pressure and massage on specific points of the body, has emerged as a treatment modality. This study aims to investigate the Effect of Acupressure Therapy on Reducing Menstrual Pain (Dysmenorrhea) among Adolescents at UPTD SMP Negeri 2 Kec. Akabiluru in 2024. The research design employed is a Quasi-experimental approach with a One Group Pretest- Posttest design. Purposive sampling was used to select participants from the entire female student population at UPTD SMP 2 Kec. Akabiluru. Bivariate analysis involved the Shapiro- Wilk test, and the research hypothesis was tested using Non-Parametric Statistical tests. The results of the univariate analysis revealed that the average level of dysmenorrhea pain among respondents before receiving acupressure therapy was 8.35, while two days after therapy, it decreased to 2.65. Bivariate analysis demonstrated a significant difference in the average pain levels before and after acupressure therapy with a p-value of 0.000. In conclusion, the study suggests that acupressure therapy effectively reduces menstrual pain (dysmenorrhea). Therefore, it is recommended that respondents consider acupressure therapy as an alternative method for alleviating menstrual pain (dysmenorrhea).Keywords: Pain, Dysmenorrhea, Acupressure